The Effect Of The Integrated Think Pair Share Problem-Based Learning Model On Students' Cognitive Learning Outcomes Of Class X SMA - Jahidin; I Wayan Suama; Fatimah Nuruttahirah (Kirana Publisher (KNPub), 2023)
The study aims to determine the effect of the integrated think pair share problem-based learning model on students' cognitive learning outcomes. This type of research design by quasi-experimental and pretest-posttest nonequivalent control group design. The population in this research were all students of X MIA SMA and the sample of this research were class X MIA 1 and class X MIA 3 SMA in the odd semester of the academic year 2022/2023. The analysis technique used for descriptive analysis to determine the score of students' cognitive learning outcomes and inferential analysis to test the research hypothesis. The results showed that the average score of the experimental class was higher than the control class of 0.75 in the experimental class and 0.52 in the control class. The results of the hypothesis test showed that 7.61 was greater than 1.67 then Ho was rejected, meaning that there was a significant effect of integrated think pair share problem-based learning model on students cognitive learning outcomes in class X SMA